PENGEMBANGAN MULTIMEDIA INTERAKTIF BAHASA ARAB TINGKAT MADRASAH TSANAWIYAH - Ningsih, Nurfitria; Lukman, Aprizal; Saharudin, Saharudin (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
This article is based on a developmental research whis is aimed at constructing Arabic interactive multimedia which is interesting, effective and giving motivation for studenst in learning Arabic. The model development employs the model of Lee & Owens development which consists of five phases: (1) analysis phase. (2) design phase. (3) development phase. (4) implementation phase. (5) evaluation phase. Based on the data analysis of development process, experts validation, and field trials of the product, it can be concluded that the quality of the Arabic interactive multimedia is good and acceptable for used as a student learning source or as teacher’s media in learning process. Keyword: Interactive multimedia, Arabic Teaching Learning